Bilateral ovarian mature teratoma with unilateral torsion in a 42 years old female in a low-income country - Garnier, Jean B.; Massena, Larry M.; Lahens, Yvan C.; Bastien, Paul D.; Milien, Christophe (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Bilateral ovarian mature teratomas are rare. They occur mostly in the reproductive age group women. Serious complications such torsion required prompt surgical intervention. No case so far has been reported in the Haitian literature. We present a case of a 42-years-old female arrived at the Centre Medical Frere after a two-day delay due to limited healthcare access, experiencing acute abdominal pain and vomiting. After clinical and ultrasound examination, we concluded to the diagnosis of ovarian torsion with patient having bilateral ovarian mass which guided us considering different parameters to a total hysterectomy with salpingo-oophorectomy. Histopathology confirmed bilateral mature teratomas with torsion. This case helps bring awareness regarding the importance of regular gynecologic follow-up, along early detection and management especially in resource-limited settings where delayed care can lead to complications.